Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content 1. Science, Technology, Engineering, and Mathematics (STEM) Education in the United States of America and Saudi Arabia: A Comparative Study Dr. Saud Mutlaq Al-Otaibi 2. Effect of regulating proportion of track students on cognitive learning outcome of natural science courses in single-track schools Mr. Mohammed Mufarrih Al-Shahrani 3. The effectiveness of a training program in improving human quality among a sample of female students at Qatar University Prof. Musalam Salim Ali Al-Waheibi 4. Employing the Short Story with Pictures to Enhance the Language Development of Deaf and Hard of Hearing Students from the Point of view of their teachers Mrs. Hessa Saleh Waqit Al-Zahrani, Dr. Omar Fawwaz Abdelaziz 5. The degree of use of the Ain educational portal in distance education and the obstacles and requirements of use from the point of view of teachers and primary school principals in the city of Abha Mrs. Manal Ali Al Saad Al-Qahtani 6. Employing Alternative Assessment Strategies and Their Obstacles from The Perspective of Arabic Language Teachers at the Secondary School Level Mrs. Wafa’a Hamed Muda Al-Alawi , Dr. Khdijah Mohamad Omar Haji 7. Academic Self-Efficacy and its relation to Academic Boredom among Umm Al-Qura University female students Mrs. Makiah Abdo Hammdi